2011
DOI: 10.1089/jwh.2011.2891
|View full text |Cite
|
Sign up to set email alerts
|

Rural Disparity in Domestic Violence Prevalence and Access to Resources

Abstract: Objective: Intimate partner violence (IPV) against women is a significant health issue in the United States and worldwide. The majority of studies on IPV have been conducted in urban populations. The objectives of this study are to determine if prevalence, frequency, and severity of IPV differ by rurality and to identify variance in geographic access to IPV resources. Methods: A cross-sectional clinic-based survey of 1478 women was conducted to measure the 1-year prevalence of physical, sexual, and psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
240
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(256 citation statements)
references
References 28 publications
13
240
0
3
Order By: Relevance
“…In addition, violence against women tends to worsen in rural areas, since they are often overlooked (6) , given the geographical distance from the urban area (7) . Thus, isolation increases the chances of these women experiencing violence (8) . Against this background, it is evident that rural women in situations of violence face numerous challenges that are manifested by the inequality of access to public services, the labor market and land tenure, which reflects in inequalities in living conditions and health (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, violence against women tends to worsen in rural areas, since they are often overlooked (6) , given the geographical distance from the urban area (7) . Thus, isolation increases the chances of these women experiencing violence (8) . Against this background, it is evident that rural women in situations of violence face numerous challenges that are manifested by the inequality of access to public services, the labor market and land tenure, which reflects in inequalities in living conditions and health (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…Rural women experience both higher rates and greater severity of IPV than their non-rural peers (Hart & Klein, 2013;Peek-Asa et al, 2011;Zakar, Zakar, & Abbas, 2016). Although the mechanisms linking geography and IPV are unclear, several factors peculiar to the rural setting have been hypothesized.…”
Section: Geographymentioning
confidence: 99%
“…Although the mechanisms linking geography and IPV are unclear, several factors peculiar to the rural setting have been hypothesized. For example, compared to their non-rural counterparts, rural women tend to have lower education and income, have stronger belief in and greater acceptance of patriarchal norms, marry at a younger age, and experience greater social isolation; all of these factors place these women at higher risk for IPV (Ackerson et al, 2008;Peek-Asa et al, 2011;WHO, 2010;Zakar et al, 2016). In fact, research has shown that rural women are 3 times further away than urban women from IPV intervention services such as emergency shelters, counselling, legal representation, transportation, and resources referral (Peek-Asa et al, 2011).…”
Section: Geographymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that female victims of intimate partner aggression living in rural areas had higher frequency and severity of abuse compared with urban victims, in part due to geographical and social isolation (Murty et al 2003;Peek-Asa et al 2011). Rural victims may also have decreased ability to cope with the aggression due to limited availability of local services (Peek-Asa et al 2011). Despite evidence that women with children and rural women are at high risk for intimate partner aggression, to our knowledge, no studies have examined intimate partner aggression among rural mothers of young children.…”
Section: Introductionmentioning
confidence: 99%